Result Proof A sequence {an} is defined recursively by a₁ = 1, a₂ = 3 and an = 2an-1 Then an = 2n - 1 for all ne N. -an-2 for n ≥ 3. We proceed by induction. Since a₁ = 2 · 1 − 1 = 1, the formula holds for n = 1. Assume for an arbitrary positive integer k that a; = 2i - 1 for all integers i with 1 ≤ i ≤k. We show that ak+1 = 2(k+ 1) − 1 = 2k + 1. If k = 1, then ak+1 = a₂ = 2·1+1 = 3. Since a2 = 3, it follows that ak+1 = 2k + 1 when k = 1. Hence, we may assume that k≥ 2. Since k + 1 ≥ 3, it follows that ak+1 = 2ak - ak-1 = 2(2k – 1) – (2k − 3) = 2k + 1, which is the desired result. By the Strong Principle of Mathematical Induction, an 2n 1 for all n € N. =
Result Proof A sequence {an} is defined recursively by a₁ = 1, a₂ = 3 and an = 2an-1 Then an = 2n - 1 for all ne N. -an-2 for n ≥ 3. We proceed by induction. Since a₁ = 2 · 1 − 1 = 1, the formula holds for n = 1. Assume for an arbitrary positive integer k that a; = 2i - 1 for all integers i with 1 ≤ i ≤k. We show that ak+1 = 2(k+ 1) − 1 = 2k + 1. If k = 1, then ak+1 = a₂ = 2·1+1 = 3. Since a2 = 3, it follows that ak+1 = 2k + 1 when k = 1. Hence, we may assume that k≥ 2. Since k + 1 ≥ 3, it follows that ak+1 = 2ak - ak-1 = 2(2k – 1) – (2k − 3) = 2k + 1, which is the desired result. By the Strong Principle of Mathematical Induction, an 2n 1 for all n € N. =
Advanced Engineering Mathematics
10th Edition
ISBN:9780470458365
Author:Erwin Kreyszig
Publisher:Erwin Kreyszig
Chapter2: Second-order Linear Odes
Section: Chapter Questions
Problem 1RQ
Related questions
Question
Please show how the highlighted part works step by step, I dont get the substitution, how do we get ak=2k-1 and
ak-1=2k-3?
![Result
Proof
A sequence {an} is defined recursively by
a₁ = 1, a₂ = 3 and an = 2an-1
Then an = 2n - 1 for all ne N.
-an-2 for n ≥ 3.
We proceed by induction. Since a₁ = 2∙1 − 1 = 1, the formula holds for n = 1.
Assume for an arbitrary positive integer k that a; = 2i - 1 for all integers i with 1 ≤ i ≤k.
We show that ak+1 = 2(k+ 1) − 1 = 2k + 1. If k = 1, then ak+1 = a₂ = 2·1+1 = 3.
Since a2 = 3, it follows that ak+1 = 2k + 1 when k = 1. Hence, we may assume that
k≥ 2. Since k + 1 ≥ 3, it follows that
ak+1 = 2ak-ak-1 = 2(2k − 1) – (2k − 3) = 2k + 1,
=
which is the desired result. By the Strong Principle of Mathematical Induction, an
2n 1 for all n € N.](/v2/_next/image?url=https%3A%2F%2Fcontent.bartleby.com%2Fqna-images%2Fquestion%2F8e237d3f-b8e6-4775-a6f9-5671b153aef2%2Fe0b06649-6a71-49b2-9636-953ac8c35e74%2Fphf8wko_processed.png&w=3840&q=75)
Transcribed Image Text:Result
Proof
A sequence {an} is defined recursively by
a₁ = 1, a₂ = 3 and an = 2an-1
Then an = 2n - 1 for all ne N.
-an-2 for n ≥ 3.
We proceed by induction. Since a₁ = 2∙1 − 1 = 1, the formula holds for n = 1.
Assume for an arbitrary positive integer k that a; = 2i - 1 for all integers i with 1 ≤ i ≤k.
We show that ak+1 = 2(k+ 1) − 1 = 2k + 1. If k = 1, then ak+1 = a₂ = 2·1+1 = 3.
Since a2 = 3, it follows that ak+1 = 2k + 1 when k = 1. Hence, we may assume that
k≥ 2. Since k + 1 ≥ 3, it follows that
ak+1 = 2ak-ak-1 = 2(2k − 1) – (2k − 3) = 2k + 1,
=
which is the desired result. By the Strong Principle of Mathematical Induction, an
2n 1 for all n € N.
Expert Solution
![](/static/compass_v2/shared-icons/check-mark.png)
This question has been solved!
Explore an expertly crafted, step-by-step solution for a thorough understanding of key concepts.
Step by step
Solved in 3 steps with 3 images
![Blurred answer](/static/compass_v2/solution-images/blurred-answer.jpg)
Follow-up Questions
Read through expert solutions to related follow-up questions below.
Follow-up Question
How do you decide that k is greater than or equal to 2, and k+1 is greater than or equal to 3?
Solution
Recommended textbooks for you
![Advanced Engineering Mathematics](https://www.bartleby.com/isbn_cover_images/9780470458365/9780470458365_smallCoverImage.gif)
Advanced Engineering Mathematics
Advanced Math
ISBN:
9780470458365
Author:
Erwin Kreyszig
Publisher:
Wiley, John & Sons, Incorporated
![Numerical Methods for Engineers](https://www.bartleby.com/isbn_cover_images/9780073397924/9780073397924_smallCoverImage.gif)
Numerical Methods for Engineers
Advanced Math
ISBN:
9780073397924
Author:
Steven C. Chapra Dr., Raymond P. Canale
Publisher:
McGraw-Hill Education
![Introductory Mathematics for Engineering Applicat…](https://www.bartleby.com/isbn_cover_images/9781118141809/9781118141809_smallCoverImage.gif)
Introductory Mathematics for Engineering Applicat…
Advanced Math
ISBN:
9781118141809
Author:
Nathan Klingbeil
Publisher:
WILEY
![Advanced Engineering Mathematics](https://www.bartleby.com/isbn_cover_images/9780470458365/9780470458365_smallCoverImage.gif)
Advanced Engineering Mathematics
Advanced Math
ISBN:
9780470458365
Author:
Erwin Kreyszig
Publisher:
Wiley, John & Sons, Incorporated
![Numerical Methods for Engineers](https://www.bartleby.com/isbn_cover_images/9780073397924/9780073397924_smallCoverImage.gif)
Numerical Methods for Engineers
Advanced Math
ISBN:
9780073397924
Author:
Steven C. Chapra Dr., Raymond P. Canale
Publisher:
McGraw-Hill Education
![Introductory Mathematics for Engineering Applicat…](https://www.bartleby.com/isbn_cover_images/9781118141809/9781118141809_smallCoverImage.gif)
Introductory Mathematics for Engineering Applicat…
Advanced Math
ISBN:
9781118141809
Author:
Nathan Klingbeil
Publisher:
WILEY
![Mathematics For Machine Technology](https://www.bartleby.com/isbn_cover_images/9781337798310/9781337798310_smallCoverImage.jpg)
Mathematics For Machine Technology
Advanced Math
ISBN:
9781337798310
Author:
Peterson, John.
Publisher:
Cengage Learning,
![Basic Technical Mathematics](https://www.bartleby.com/isbn_cover_images/9780134437705/9780134437705_smallCoverImage.gif)
![Topology](https://www.bartleby.com/isbn_cover_images/9780134689517/9780134689517_smallCoverImage.gif)